PENYULUHAN PENGGUNAAN OBAT BIJAK (DAGUSIBU) PADA MASYARAKAT DI DESA LABUAN BAJO BUTON UTARA - Restu Nur Hasanah Haris; Nur Fitriana Muhammad Ali; Hesti Trisnianti Burhan; Wa Ode Masrida; Ikhsan Sidiq; Irwan Irwan; Rezky Dwi Fitriani (Universitas Halu Oleo, 2022)
The use of drugs among the community is useful for providing self-improvement. Communities independently are accustomed to using drugs in everyday life. The lack of access to health in rural areas and the provision of wrong information can have risks and harmful effects for oneself. Need knowledge regarding how to use drugs that are good and right. The DAGUSIBU program is an alternative that can be given to provide education and information for the community. The purpose of this counseling is to provide education and information related to the use of sage medicine with the DAGUSIBU principle. Counseling was carried out in Labuan Bajo Village, North Buton Regency. The material was delivered directly by the pharmacist using interactive lecture and discussion methods, followed by the people of Labuan Bajo Village. The material presented is related to how to get the right and proper medicine, how to use the medicine, how to store the medicine and how to dispose/destroy the medicine. The result of this activity is that the community has received proper information about the use of drugs where previously knowledge about drug use was still lacking. In the future, with the information and knowledge that you already have, you can create a society that is aware of drugs and minimizes the use of wrong drugs in the community.